Genetic variation in phenylketonuria: analysis of the PAHvdb database - Alin Remus Iuhas; Claudia Jurca; Marius Bembea (Amaltea Medical Publishing House, 2022)
Introduction. Phenylketonuria (PKU) is the most frequent inborn metabolism error. The principal determinant factor for the metabolic phenotype in PKU is the residual enzymatic activity, which is determined by the variations in the phenylalanine hydroxylase (PAH) gene. To date, there are known over 1200 PAH gene variants contained in the PAH International Database of Variations in Phenylalanine Hydroxylase Gene (PAHvdb). Aim. The aim of this study is to elaborate an updated PAH variant report with their type, localization, frequency and severity. Material and method. The PAH variant analysis was made using PAHvdb. PAHvdb presently contains 1285 PAH variants and is connected to BIOPKU genotype-phenotype database which has anonymized information from nearly 18000 PKU patients, with data regarding the genotype and the correspondent phenotype. Results. From the 1285 studied variants, the most frequent variants are substitutions - 1051 (81.8%) and deletions - 150 (11.7 %). The majority (723 - 56.3%) is represented by missense mutations, followed in frequency by frameshift variants- 177 (13.8%), splice ESS (Exonic Splicing Silencer) variants - 127 (9.9%) and nonsense mutations - 86 (6.7%). The most affected region of the gene is exon 6 (169 variants), followed by exon 7 (151 variants), exon 3 (130 variants) and exon 11 (121 variants). The majority of variants are located in the catalytic (57.66%) domain. The most frequent 3 alleles are c.1222C>T with a frequency of 19,2%, c.1066-11G>A with a frequency of 6,8% and c.782G>A with a frequency of 5.5%. From the total 1285 variants, 488 (38.5%) cause a severe phenotype, 57 (4.9%) cause a moderate phenotype and 74 (6%) cause a mild phenotype; in the case of 666 variants (50,6%) which have a low allelic frequency the metabolic phenotype couldn't be established. Discussions. The majority of the variants are substitutions, missense in the catalytic domain of the gene, on the 6th exon. Approximatively 50% of the alleles are found in single patients so they can't be used for phenotypic prediction. The majority of variants are causing a severe phenotype. Conclusion. The existence of a database with a large number of PKU patients and PAH variants brings an important contribution to the understanding of the genotype-phenotype relation and to the capacity of better phenotypical prediction based on genotype.